The effect of a-terpineol on cell cycle, apoptosis and Bcl-2 family protein expression of breast cancer cell line MCF-7 - Damiana Sapta Candrasari; Sofia Mubarika; Mae Sri Hartati Wahyuningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
ABSTRACT The cytotoxic activity of a-terpineol on T47D and HeLa cancer cell lines have been reported. This study was conducted to evaluate the effect of a-terpineol on cell cycle, apoptosis and Bcl-2 as well as Bax expression on MCF-7 cell line. The cytotoxic activity of a-terpineol was determined using MTT cell assay. Cell cycle and apoptosis were analysed using flowcytometry, whereas Bcl-2 and Bax expression were evaluated using immunohistochemistry. The results showed that a-terpineol had cytotoxic effect on the MCF-7 cell lines with an IC50 value of 33.0 ± 5.4 μg/mL. a-Terpineol induced cell accumulation in Sub-G1 lead to apoptosis of the MCF-7 cell. Moreover, a-terpineol inhibited Bcl-2 and induced Bax expressions. In conclusion, a-terpineol has potential anticancer activity against MCF-7 cancer cell line trough through cells cycle inhibition and apoptosis stimulation.